2012
DOI: 10.1165/rcmb.2012-0057oc
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Inhibitory Prostaglandin E2 Signaling in Human Lung Fibroblasts Is Mediated by Phosphodiesterase 4

Abstract: The etiology of chronic obstructive pulmonary disease (COPD) is complex and involves an aberrant inflammatory response. Prostaglandin (PG)E2 is elevated in COPD, is a key modulator of lung fibroblast functions, and may influence COPD progression. Most studies evaluating the effects of PGE2 on lung fibroblasts have used acute exposures. The current study evaluated whether longer-term exposure would induce attenuation of PGE2 signaling as part of an autoregulatory pathway. Human fetal lung fibroblasts were pretr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Interestingly, pretreatment with PGE 2 resulted in augmentation of contraction. The mechanism of this effect of PGE 2 pretreatment is not defined, but it resembles the results of Michalski who observed augmentation of chemotaxis following PGE 2 pretreatment [15]. PGE 2 pretreatment also changed the response of the fibroblasts to salmeterol and cilomilast added alone.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Interestingly, pretreatment with PGE 2 resulted in augmentation of contraction. The mechanism of this effect of PGE 2 pretreatment is not defined, but it resembles the results of Michalski who observed augmentation of chemotaxis following PGE 2 pretreatment [15]. PGE 2 pretreatment also changed the response of the fibroblasts to salmeterol and cilomilast added alone.…”
Section: Discussionmentioning
confidence: 71%
“…We have shown that PGE 2 exposure augments PDE4 activity and induces functional homologous and heterologous attenuation of cAMP-mediated inhibition of fibroblast chemotaxis [15]. Similarly, PDE4 activity induced by PGE 2 is involved in the desensitization of β -mimetics in human myometrium during the late stages of pregnancy [16].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, PGE 2 levels remain elevated in fibrotic lungs, so the reason for its limited antifibrotic action in PF is not explained. It is possible that PGE 2 loses its antifibrotic action following long-term exposure due to attenuated cAMP signaling in lung fibroblasts (Michalski et al 2012). Because PF is characterized by ongoing airway injury and presumably chronic elevation of PGE 2 (Fastres et al 2017), the current study examined how EP receptor signaling is affected by prolonged agonist exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PF fibroblast cells are refractory to PGE 2 receptor responses (Bozyk and Moore 2011), presumably diminishing the antifibrotic action of PGE 2 . Fibroblasts isolated from patients with chronic obstructive pulmonary disease also have altered responses to PGE 2 as compared to those from normal subjects (Michalski et al 2012). Thus, we hypothesize that PGE 2 effects are self-limiting because of desensitization caused by prolonged agonist activation of EP receptors.…”
Section: Introductionmentioning
confidence: 89%
“…This compound has a functional EP2 K B of 8.8 nM, and with a systemic administration in mice it showed a plasma half-life of 2.7 h and a brain-to-plasma ratio of 0.02 . The low brain penetration of compounds 5 and 7 enables these two compounds to be ideal tools to study the functions of the EP2 receptor in peripheral diseases associated with chronic inflammation such as rheumatoid arthritis and chronic obstructive pulmonary disease, in which EP2 appears to play essential pathogenic roles. Molecular docking using the recently solved cryo-electron microscopy (cryo-EM) structure of the human EP2 receptor and G s protein complex (PDB code: 7CX3) revealed the simulated interactions between the EP2 receptor and Emory compounds using Schrödinger software, , exemplified by compound 3 (Figure ). Understanding the dynamic three-dimensional (3-D) interactions between these competitive antagonists and the EP2-G s complex might help with better rational designs to develop the next-generation EP2 antagonists with more balanced potency and selectivity.…”
Section: Ep2 Antagonistsmentioning
confidence: 99%